Development of Flat Solid Figure Learning Design based Rejang Lebong Ethnomathematics - Agung Setia Budi; Armiati; Edwin Musdi; Ali Asmar (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
This study aims to produce a learning design for flat-sided geometry based on Rejang Lebong ethnomathematics to improve students' mathematical problem-solving skills that are valid, practical, and effective. It is motivated by the low ability to solve students’ mathematical problems. Mathematics learning carried out in schools should involve students actively. The research procedure is guided by the Plomp development design. The development model studied by Plomp is the initial investigation, development, prototyping, and research phases. In the initial investigation phase, the implementation of needs, curriculum, concept, and student analyses was implemented. In the prototype development phase, formative evaluation consists of self-evaluation, one-on-one evaluation, one-on-one evaluation, small group evaluation, and testing. Meanwhile, at the time of its application, it was tested on students of class VIII SMP to see the learning outcomes of the learning problem-solving abilities. Based on the development that has been carried out, it is obtained that the learning design of flat-sided geometry based on the Rejang Lebong ethnomathematics in the form of HLT, teacher's books, and books for class VIII SMP students are valid, practical, and effective.